(untitled) (London Journal of Research In Humanities and Social Sciences, 2025)
This scholarly investigation delves into the personal journeys of three remarkable first-generation Mexican American women who pursued a Ph.D. despite the many obstacles they faced. While two of these women have already achieved tenure, the third is currently in her first year of doctoral studies. Throughout the ups and downs of their academic pursuits, these women frequently experienced self-doubt and struggled to compete with peers who had greater access to scholarships and grants. Nevertheless, they chose to embrace this once-in-a-lifetime opportunity and were unwavering in their determination to make the most of it. Each has a unique story of what motivated them to persevere, but one common thread is the reward of earning a PhD ultimately exceeded any hardships they encountered along the way. Their incredible life experiences can inspire others to aim high and pursue their dreams. By utilizing analytical lenses grounded in ethnography and constructivist theory, this study provides valuable insight into the social dynamics and personal experiences of first-generation college students who aspire to complete a doctoral program.